Socio-Economic Responsibility of Pharmaceutical Companies: Bangladesh Case - Akter, Nahid (Asian Business Review, 2018)
Bangladesh is a rustic of rising economy. The causes of its rising is high rate of industrialization and investment in different sectors. The pharmaceutical sector that is the second largest export earning source of the country after Ready Made Garments contributes almost 1% of the GDP and is currently the third largest tax paying sector in the country. Square Pharmaceutical Limited (SPL) the biggest name in the pharmaceutical sector of Bangladesh has a market share of 19.3% and the total exporting amount become BDT 1,137.99 millions in FY 2016-2017 that is 34.46% more than the previous year. This paper is almost done using the secondary data though a slight primary data is used where customer’s choice is examined where the highest 38% of the customer like the brand name square. This study assessed and examined the role of pharmaceutical company to the economy of Bangladesh from the perspective of square pharmaceutical limited as the sample company. The researcher also investigates the corporate social responsibility activities played by the respective company. This paper will be useful to the pharmaceutical companies, concerned authorities, policy makers and the government to know the role of pharmaceutical sector and required initiatives to eliminate all the hindrances and resolve all the problems to make out pharmaceutical sector as a crucial actor in both domestic and international market.